Breadth and Depth of Academic Vocabulary Knowledge: Assessing their roles in Academic Reading and Writing of English Language Learners - Lee, Chew Wei; Rethinasamy, Soubakeavathi (2017)
The study investigated the relationship between English language learner’s (ELL) academic vocabulary and their performance in academic reading and writing. The specific objectives were to determine the relationship between breadth and depth of academic vocabulary knowledge and the academic reading comprehension and writing of ELL and to find out the extent to which scores on breadth and depth of academic vocabulary knowledge contribute to ELL’s performance in academic reading and writing. Quantitative research design was employed in the study where language tests which were Vocabulary Levels Test (VLT), the Productive Vocabulary Levels Test (PVLT), the Depth of Vocabulary Knowledge (DVK) Test, a Reading Comprehension (RC) test and a Writing Composition were administered to 90 UniversitiMalaysia Sarawak (UNIMAS) undergraduates. For the analysis, Pearson correlation and multiple linear regression were used. Pearson correlation analysis showed that there was a positive correlation between breadth and depth of academic vocabulary with both academic reading comprehension and writing performance of ELL in UNIMAS. Vocabulary depth had a stronger correlation with academic reading comprehension while vocabulary breadth had a stronger correlation with academic writing. Both dimensions of vocabulary knowledge were positively correlated with each other. The analysis of multiple linear regression revealed that both dimensions of academic vocabulary knowledge contributed a moderate proportion to the variance of academic reading comprehension and writing although vocabulary depth predicted more to the overall variance of academic reading comprehension while vocabulary breadth was a more powerful predictor of ELL’s performance in academic writing. Both breadth and depth of academic vocabulary knowledge were powerful predictors of reading comprehension and writing performance of learners and therefore a combination of these two dimensions will aid in better performance rather than just one alone.Thus, the teaching and learning of the English language should emphasize in vocabulary building in terms of enriching learners’ vocabulary storage as well as improving the usage of vocabulary in context by understanding the meaning.